Korean War : almanac and primary sources - Benson, Sonia; Raffaelle, Gerda-Ann (Detroit, Mich. : U. X. L., 2002)
A comprehensive overview of the Korean War, including biographies and full or excerpted memoirs, speeches, and other source documents
Includes bibliographical references and index
Keywords: Korean War, 1950-1953 -- Juvenile literature; Korean war, 1950-1953; Korean War, 1950-1953 -- Sources; Korea -- History -- 20th century -- Juvenile literature